Preventing childhood obesity by reducing consumption of carbonated drinks: cluster randomised controlled trial. Issue 7450 (23rd April 2004) - James, Janet; Thomas, Peter; Cavan, David; Kerr, David
Abstract: Objective To determine if a school based educational programme aimed at reducing consumption of carbonated drinks can prevent excessive weight gain in children. Design Cluster randomised controlled trial. Setting Six primary schools in southwest England. Participants 644 children aged 7-11 years. Intervention Focused educational programme on nutrition over one school year. Main outcome measures Drink consumption and number of overweight and obese children. Results Consumption of carbonated drinks over three days decreased by 0.6 glasses (average glass size 250 ml) in the intervention group but increased by 0.2 glasses in the control group (mean difference 0.7, 95% confidence interval 0.1 to 1.3). At 12 months the percentage of overweight and obese children increased in the control group by 7.5%, compared with a decrease in the intervention group of 0.2% (mean difference 7.7%, 2.2% to 13.1%). Conclusion A targeted, school based education programme produced a modest reduction in the number of carbonated drinks consumed, which was associated with a reduction in the number of overweight and obese children.